Pemberdayaan masyarakat berkonsep pembangunan berkelanjutan (SDGs) dalam kegiatan kuliah kerja nyata Universitas Gadjah Mada di masa pandemi Covid-19 - Djarot Heru Santosa (Unri Conference Series: Community Engagement, 2020)
Gadjah Mada University (UGM) students conducted community empowerment activity in providing service to the community during the Covid-19 Pandemic era through Student Community Services Learning (SCL)Program. The goal was to help deal with the Covid-19 Pandemic impacted the community from various sectors, such as social, economic, education, culture, using various science and technology, especially internet-communication, to support the education. The SCL program is carried out in the emergency response and the recovery phase. The implementation was determined based on the UGM Chancellor's Circular. Operational implementation in the field during the emergency response phase was carried out through assistance in understanding and mitigating the Covid-19 pandemic. The results of SCL activities during the pandemic showed a real contribution in handling the emergency response period and the recovery period of the impact of the Covid-19 Pandemic. The approach is taken by prioritizing the humanities' social approach, namely paying attention to the community's background, local elements, equality, customs, and culture, and the conditions in the society it faces.